Menanam Benih Kesalehan: Membentuk Karakter Islami Siswa melalui Religious Culture - Riany, Helifsia; Hartati, Zainap; Muslimah, Muslimah (ALSYS, 2023)
The multidimensional crisis that is currently happening to the Indonesian state, if we look for the causes of the problem, comes from weak development of the nation and character which causes moral and moral shifts for the nation's successors such as becoming perpetrators of physical and psychological violence. This study aims to describe the Islamic character of students at Sekolah Sahabat Alam Palangka Raya and to describe the formation of Islamic character in students through religious culture at Sekolah Sahabat Alam Palangka Raya. This research uses descriptive qualitative method. Data collection techniques are observation, interviews and documentation. The results showed that: 1) the character of the students at Sekolah Sahabat Alam Palangka Raya can be said to have good Islamic character. This can be seen from their independent attitude which spontaneously applies religious habituation activities in behaving so that they are well organized without any encouragement or coercion. 2) the formation of the Islamic character of students through religious culture at Sekolah Sahabat Alam Palangka Raya, namely when reciting the Koran, traveling around nature, camping and exploring the environment around the school, praying dhuha in congregation, shaking hands and greeting teachers and students and teachers of the opposite sex do not shake hands directly . In addition, love the environment by disposing of trash in its place.